Criminalizing medical research fraud: Towards an appropriate legal framework and policy response. (March 2019) - Leung, Gilberto K.K.
Increasing concerns about the societal impact of medical research fraud have led to calls for its criminalization within the United Kingdom, but there has been little discussion of how the criminal law could be applied in this context. The author proposes a legal framework whereby acts of falsification or fabrication may be prosecuted under a general offence of fraud contained within the Fraud Act 2006 in England and Wales. The threshold for prosecution may be determined by assessing the effect of an act on the reliability and robustness of research findings and using a Two-stage Full Code Test modelled on the Crown Prosecution Service Policy for Prosecutors in Respect of Cases of Encouraging or Assisting Suicide . This provides a pragmatic approach to handling an unyielding problem that affects many sectors of society and necessitates the implementation of an explicit government policy aimed at balancing the protection of public interests against the promotion of medical advancement.